Response of Runoff and Sediment Yield from Maize Slope Farmland in Karst Areas to Slope Gradient - WU Guangqin; DAI Quanhou; WANG Yong; DING Pengwei; YAO Yiwen (Shuitu Baochi Xuebao, 2024)
[Objective] To elucidate the responses of surface runoff, subsurface runoff, and underground runoff hydrological pathways to slope in maize sloping farmland in Karst regions. [Methods] Taking the karst maize slope in Guizhou Province as the research object, the artificial simulated rainfall test method was used to investigate the effects of different slopes (5°, 10°, 15°, 20°, 25°) on the runoff and sediment yield patterns of various hydrological pathways under the same rainfall intensity (60 mm/h). [Results] (1) Surface runoff and sediment yield showed a very significant positive correlation with slope gradient at the level of 0.01 (p<0.01). The maximum runoff modulus and maximum sediment yield modulus were 0.18 L/(min·m2) and 13.12 g/(min·m2) respectively. Surface sediment yield changed from sheet erosion to rill erosion during the 10~30 min period. (2) The maximum runoff coefficient was 49% when the subsurface runoff was at a moderate slope (15°), and there was a highly significant positive correlation between runoff yield, as well as sediment yieldand slope gradient. Although the correlation between underground runoff or sediment production and slope gradient was not significant, the proportion of underground runoff was still affected the greatest by slope gradient. (3) The total sediment yield on the surface was greater than that in the soil layer and subsurface. The fitting relationship between the three different hydrological paths (surface, soil layer, and subsurface) and slope gradient was surface runoff > interflow > subsurface runoff. [Conclusion] In the maize slope farmland in karst areas, as the slope gradient increases, the soil erosion patterns of different soil layers show inconsistency, and the main form of soil erosion is surface erosion, supplemented by underground leakage. The maize canopy can slow down the evolution of surface soil erosion forms at small slope gradients. The research results can provide theoretical reference for estimating soil erosion in karst maize sloping farmland and maize planting strategies.